Uncovering the Oral Dysbiotic Microbiota as Masters of Neutrophil Responses in the Pathobiology of Periodontitis - Prucsi, Zsombor; Płonczyńska, Alicja; Potempa, Jan; Sochalska, Maja (Frontiers in Microbiology, 2021)
Numerous bacterial species participate in the shift of the oral microbiome from beneficial to dysbiotic. The biggest challenge lying ahead of microbiologists, immunologists and dentists is the fact that the bacterial species act differently, although usually synergistically, on the host immune cells, including neutrophils, and on the surrounding tissues, making the investigation of single factors challenging. As biofilm is a complex community, the members interact with each other, which can be a key issue in future studies designed to develop effective treatments. To understand how a patient gets to the stage of the late-onset (previously termed chronic) periodontitis or develops other, in some cases life-threatening, diseases, it is crucial to identify the microbial composition of the biofilm and the mechanisms behind its pathogenicity. The members of the red complex (Porphyromonas gingivalis, Treponema denticola, and Tannerella forsythia) have long been associated as the cause of periodontitis and stayed in the focus of research. However, novel techniques, such as 16S clonal analysis, demonstrated that the oral microbiome diversity is greater than ever expected and it opened a new era in periodontal research. This review aims to summarize the current knowledge concerning bacterial participation beyond P. gingivalis and the red complex in periodontal inflammation mediated by neutrophils and to spread awareness about the associated diseases and pathological conditions.